PENYELESAIAN SENGKETA DALAM PERJANJIAN PINJAM PAKAI TANAH BERDASARKAN HUKUM PERDATA (Studi Kasus Kampung Dayun Siak) - Hafiiz Adri Junyes; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This study aims to determine the implementation of the Lend-UseAgreement between the first party and the second party, and efforts to resolvedisputes in the Lend-Use Agreement between the first party and the second partybased on civil law. This research is useful theoretically and practically. The typeof research is sociological juridical law research. Based on the results of the study,it was shown that the implementation of the Lend-Use Agreement between theFirst Party and the Second Party was carried out verbally with the object of theagreement being foodcrop land. In the agreement, it was agreed that the mainprovisions were that the Second Party was only allowed to plant foodcrops. Theagreement that has been made above has explained the existence of the partiesrelated to the rights and obligations of each party, on that basis the agreement thathas been made between the two parties has fulfilled the legal requirements of theagreement as stipulated in Article 1320 of the Indonesian Civil Code. However, inits implementation, the Second Party does not follow the agreement that has beenmade, resulting in a default. The settlement of disputes between the first party andthe second party in the Lend-Use Agreement in Berumbung Baru Village, DayunDistrict, Siak Regency has been carried out through non-litigation and litigation.However, these efforts could not solve the problem. The inhibiting factors forresolving land-borrowing disputes through mediation and litigation are notresolved because there is no goodwill from the Second Party, and this causes theproblems that have occurred to date have not been resolved.Keywords: Dispute - Agreement - Lend Use Agreement - Private Law